Access in all areas? a round up of developments in market access and health technology assessment: part 4 - Alice Beattie; Catrin Treharne; Sreeram V Ramagopalan (Becaris Publishing Limited, 2024)
In this latest update, we look at recent developments in market access including the pricing agreement of Libmeldy by the Beneluxa Initiative, the financial impact of managed entry agreements in Italy and the restructuring of Agenzia Italiana del Farmaco (AIFA). We also highlight the collaboration between FINOSE and the New Expensive Drug (NED) section of the Nordic Pharmaceutical Forum.